Front of neck access: A survey among anesthetists and surgeons - Cyprian Mendonca; Imran Ahmad; Achuthapillai Sajayan; Rathinavel Shanmugam; Manu Sharma; Will Tosh; Emily Pallister; Peter K Kimani (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Emergency front of neck access (FONA) is the final step in a Can't Intubate-Can't Oxygenate (CICO) scenario. In view of maintaining simplicity and promoting standardized training, the 2015 Difficult Airway Society guidelines recommend surgical cricothyroidotomy using scalpel, bougie, and tube (SBT) as the preferred technique. Material and Methods: We undertook a survey over a 2-week period to evaluate the knowledge and training, preferred rescue technique, and confidence in performing the SBT technique. Data were collected from both anesthetists and surgeons. Results: One hundred and eighty-nine responses were collected across four hospitals in the United Kingdom. The majority of participants were anesthetists (55%). One hundred and eleven (59%) respondents were aware of the national guidelines (96.2% among anesthetists and 12.9% among surgeons). Only 71 (37.6%) respondents indicated that they had formal FONA training within the last one year. Seventy-five anesthetists (72.8%) knew that SBT equipment was readily available in their department, while most surgeons (81.2%) did not know what equipment available. One hundred and five (55.5%) respondents were confident in performing surgical cricothyroidotomy in a situation where the membrane was palpable and only in 33 (17.5%) where the cricothyroid membrane was not palpable. Conclusion: This survey has demonstrated that despite evidence of good training for anesthetists in FONA, there are still shortfalls in the training and knowledge of our surgical colleagues. In an emergency, surgeons may be required to assist or secure an airway in a CICO situation. Regular multidisciplinary training of all clinicians working with anesthetized patients should be encouraged and supported.